2015
DOI: 10.3329/baj.v18i1.25570
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Performance of Tidal Local Aman Rice as Influenced by USG Application at Non Tidal Condition

Abstract: An experiment was carried out at research field of Bangladesh Rice Research Institute, Gazipur to evaluate the performance of tidal local aman rice as influenced by urea super granule (USG) at non-tidal condition. Four tidal local aman varieties such as Sadamota, Razashail, Kutiagoni and Kalagura were used as planting materials. Nitrogen was applied as USG (1.8g) at 10 days after transplanting (DAT), 25 DAT, before panicle initiation (BPI) stage (date of PI stage of these 4 varieties were identified from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, many earlier studies showed that the yield of rice increased with DPUSG compared to top dressing of urea (Gregory et al, 2010;Bandaogo et al, 2015). However, Abedin et al (2015) found no significant yield variation with the application of N in landrace rice. The harvest index (HI) of Kutiagni differed significantly with N fertilization (Table 2).…”
Section: Yield Components and Grain Yieldmentioning
confidence: 92%
“…Moreover, many earlier studies showed that the yield of rice increased with DPUSG compared to top dressing of urea (Gregory et al, 2010;Bandaogo et al, 2015). However, Abedin et al (2015) found no significant yield variation with the application of N in landrace rice. The harvest index (HI) of Kutiagni differed significantly with N fertilization (Table 2).…”
Section: Yield Components and Grain Yieldmentioning
confidence: 92%